Development of Wireless Smart Sensor for Structure and Machine Monitoring - Achmad Widodo; Latief Rozaqi; Ismoyo Haryanto; Djoeli Satrijo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Vibration based condition monitoring is a method used for determining the condition of a system. The condition of mechanical or a structural system can be determined from the vibration. The vibration that is produced by the system indicates the condition of a system and possibly used to calculate the lifetime of a system or even used to take early action before fatal failure occurred. This paper explains how the wireless smart sensor can be used to identify the health condition of a system by monitoring the vibration parameters. The wireless smart sensor would continuously  senses the vibration parameters of the system in a real-time systems and then data will be transmitted wirelessly  to a base station which is a host PC used for digital signal processing, from there the vibration will be plotted as a graph which used to analyzed the condition of the system. Finally, several tested performed to the real system to verify the accuracy of a smart sensor and the method of condition based monitoring.